2018
DOI: 10.1186/s12916-018-1093-8
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-guided versus traditional clinical dosing of warfarin in patients of Asian ancestry: a randomized controlled trial

Abstract: BackgroundGenotype-guided warfarin dosing has been shown in some randomized trials to improve anticoagulation outcomes in individuals of European ancestry, yet its utility in Asian patients remains unresolved.MethodsAn open-label, non-inferiority, 1:1 randomized trial was conducted at three academic hospitals in South East Asia, involving 322 ethnically diverse patients newly indicated for warfarin (NCT00700895). Clinical follow-up was 90 days. The primary efficacy measure was the number of dose titrations wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 30 publications
3
31
0
Order By: Relevance
“…standard dosing. Similar results were found by Syn et al 24 in Asian patient population on warfarin therapy. Li et al 25 have also utilized back propagation neural network model for predicting the warfarin maintenance dose after heart valve replacement.…”
Section: Ai Clinical Applications and Cardiovascular Drug Therapysupporting
confidence: 90%
See 1 more Smart Citation
“…standard dosing. Similar results were found by Syn et al 24 in Asian patient population on warfarin therapy. Li et al 25 have also utilized back propagation neural network model for predicting the warfarin maintenance dose after heart valve replacement.…”
Section: Ai Clinical Applications and Cardiovascular Drug Therapysupporting
confidence: 90%
“…[19][20][21][22] There are several cardiovascular drugs which are being explored as therapeutic targets including clopidogrel, warfarin, and statins particularly simvastatin. [21][22][23][24] Interestingly, pharmacogenomics and precision medicine has already made a big impact on the warfarin dosing in different patient populations as shown in the randomized clinical trials done by Pirmohamed et al 23 and Syn et al 24 Pirmohamed et al 23 showed that the patients on pharmacogenetic-based warfarin dosing had greater time in the therapeutic international normalized ratio (INR) range than the patients with Hidden layers can be from one to several layers.…”
Section: Ai Clinical Applications and Cardiovascular Drug Therapymentioning
confidence: 99%
“…Subsequently, GBWD had less of an effect on anticoagulation control, and multiple-dose titrations might have had a greater role. The finding that the TTR was shorter in the GBWD group is similar to that observed in the GIFT, EU-PACT, and COUMAGEN-II trials Wen et al, 2017) but different from that in the COAG study and other Asian-based studies Gage et al, 2017;Syn et al, 2018;Zhe et al, 2018). Our study revealed that GBWD resulted in a lower prevalence of bleeding events related to anticoagulation therapy, which may have been due to superior primary outcomes.…”
Section: Discussionsupporting
confidence: 71%
“…Consistent with these findings, a more recent randomized clinical trial by Syn et al, 9 involving 322 patients of Asian ancestry, found that, when starting anticoagulation, PGx algorithms were superior to traditional dosing at guiding warfarin therapy during the first 2 weeks, and also accurately predicted maintenance dosing. As more time passes, many of the current controversies regarding PGx testing may be settled, and the growing body of convincing evidence emerging from clinical trials will likely reiterate the need to conduct preemptive PGx testing 9 …”
Section: Introductionmentioning
confidence: 73%
“…Additionally, the Genetic Informatics Trial (GIFT) demonstrated that genotype‐guided dosing of warfarin was able to lower the risk of major haemorrhage, venous thrombus/embolism and death among patients undergoing elective hip/knee joint replacement and receiving warfarin therapy during the perioperative period, when compared with routine clinical drug dosing 8 . Consistent with these findings, a more recent randomized clinical trial by Syn et al, 9 involving 322 patients of Asian ancestry, found that, when starting anticoagulation, PGx algorithms were superior to traditional dosing at guiding warfarin therapy during the first 2 weeks, and also accurately predicted maintenance dosing. As more time passes, many of the current controversies regarding PGx testing may be settled, and the growing body of convincing evidence emerging from clinical trials will likely reiterate the need to conduct preemptive PGx testing 9 …”
Section: Introductionmentioning
confidence: 85%